2021
DOI: 10.1636/joa-s-19-068
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the male genitalia of the Cacodemoniini (Pseudoscorpiones: Withiidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As shown by Mahnert (1975) and Romero-Ortiz and Sarmiento (2021) , there is morphological correspondence with genera, and Harvey (2004) suggested that the triangular dorsal apodeme shape found in many withiids likely represented a monophyletic group, the Cacodemoniini . Romero-Ortiz and Sarmiento (2021) were able to define individual Neotropical genera using the morphology of the male genitalia, which is here extended to Oligowithius , which is clearly defined based on its genitalia, among other characters. In future, an assessment of the female genitalia may provide further diagnostic features.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As shown by Mahnert (1975) and Romero-Ortiz and Sarmiento (2021) , there is morphological correspondence with genera, and Harvey (2004) suggested that the triangular dorsal apodeme shape found in many withiids likely represented a monophyletic group, the Cacodemoniini . Romero-Ortiz and Sarmiento (2021) were able to define individual Neotropical genera using the morphology of the male genitalia, which is here extended to Oligowithius , which is clearly defined based on its genitalia, among other characters. In future, an assessment of the female genitalia may provide further diagnostic features.…”
Section: Discussionmentioning
confidence: 96%
“…Terminology and measurements largely follow Chamberlin (1931b) , except for the nomenclature of the pedipalps, legs, and, with some minor modifications, the terminology of the trichobothria where we follow Harvey (1992) , chelicera ( Harvey and Edward 2007 ; Judson 2007 ) and faces of the appendages ( Harvey et al 2012 ). Male genitalia terminology follows Romero-Ortiz and Sarmiento (2021) .…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Genitalic characters are only infrequently considered in taxonomic studies of Pseudoscorpiones, primarily owing to the internal location that requires preparation and partial destruction of the specimens for examination [103]. Pseudoscorpion genitalia have been considered useful for diagnoses at higher taxonomic levels [103,104], but they have hardly ever been used for delineation at the species level [37,105,106]. For Cheliferidae, and for Dactylochelifer in particular, Vachon [37] proposed that the configuration of the median cribriform plate in female genitalia could be useful for species discrimination.…”
Section: Discussionmentioning
confidence: 99%